Funding of Clinical Trials and Reported Drug Efficacy - Oostrom, Tamar (Journal of Political Economy, 2024)
This paper estimates the effect of financial sponsorship of clinical trials on reported drug efficacy, leveraging the insight that the exact same pairs of drugs are often compared in different trials conducted by parties with different financial interests. I assemble new psychiatric trial data to estimate that a drug appears substantially more effective when the trial is sponsored by that drug’s manufacturer, compared with the same drug tested against the same combination of drugs but without sponsorship. This difference is not explained by observable characteristics, but publication bias is important. Preregistration may be effective in overcoming this bias.